2021
DOI: 10.3982/ecta16413
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Weak Identification in Semiparametric Models

Abstract: We provide general formulation of weak identification in semiparametric models and an efficiency concept. Weak identification occurs when a parameter is weakly regular, that is, when it is locally homogeneous of degree zero. When this happens, consistent or equivariant estimation is shown to be impossible. We then show that there exists an underlying regular parameter that fully characterizes the weakly regular parameter. While this parameter is not unique, concepts of sufficiency and minimality help pin down … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“… Kaji (2021) studied weakly identified parameters in semiparametric models, and introduced a notion of weak efficiency for estimators. Weak efficiency is necessary, but not in general sufficient, for decision‐theoretic optimality (e.g., admissibility) in many contexts. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“… Kaji (2021) studied weakly identified parameters in semiparametric models, and introduced a notion of weak efficiency for estimators. Weak efficiency is necessary, but not in general sufficient, for decision‐theoretic optimality (e.g., admissibility) in many contexts. …”
mentioning
confidence: 99%
“…Prior work byKaji (2021) also analyzes weak identification using paths satisfying (2).6 The more general assumption that θ * is local to 0 yields a limit experiment similar to that derived below, at the cost of heavier notation. Hence, we focus on the case with θ * ∈ 0 .…”
mentioning
confidence: 99%
“…3 Kaji (2020) studies weakly identified parameters in semiparametric models, and introduces a notion of weak efficiency for estimators. Weak efficiency is necessary, but not in general sufficient, for decisiontheoretic optimality (e.g.…”
mentioning
confidence: 99%